Official Development Assistance and Private Voluntary Support for Reproductive, Maternal, Neonatal, and Child Health in Guinea-Bissau: Assessing Trends and Effectiveness - Anaxore Casimiro; Joana Branco; Réka Maulide Cane; Michel Jareski Andrade; Luís Varandas; Isabel Craveiro (Children, 2025)
Background: Reproductive, maternal, neonatal, and child health (RMNCH) remains a key priority for official development assistance and private voluntary assistance (ODA+) in low-income countries. In Guinea-Bissau, maternal and child mortality rates remain high, with the healthcare system heavily dependent on foreign aid. This study analyzes ODA+ trends for RMNCH in Guinea-Bissau from 2002 to 2018 and assesses its impact on maternal, neonatal, infsupplent, and under-five mortality rates. Methods: We used data from the OECD Creditor Reporting System and applied the Muskoka2 methodology to estimate RMNCH-related disbursements. Funding trends were categorized by donor type and RMNCH subsectors. A longitudinal analysis used regression models to assess the relationship between aid categories and mortality outcomes. Results: RMNCH funding accounted for 8.9% of total ODA+ to Guinea-Bissau, with most aid directed toward child health. Models revealed a negative association between child health funding and under-five and infant mortality, while reproductive health funding showed no significant correlation with maternal or neonatal mortality. Conclusions: Although variable, ODA+ for RMNCH in Guinea-Bissau has helped reduce child mortality. However, maternal and neonatal mortality require targeted interventions and improved coordination. Fluctuating aid disbursements emphasize the need for sustainable health financing and stronger donor alignment with national priorities.